2016
DOI: 10.1139/cjps-2015-0255
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular responses of herbaceous peony to high temperature stress

Abstract: To clarify the theoretical basis of the differences in high temperature stress tolerance among herbaceous peony (Paeonia lactiflora Pall.), we investigated the heat injury index of twelve P. lactiflora cultivars. Of these, heat-tolerant 'Zifengyu' and moderately heat-tolerant 'Hongyanzhenghui' were selected to study the biochemical and molecular responses to high temperature stress. 'Zifengyu' had reduced malondialdehyde (MDA) content, increased soluble sugar, chlorophyll (Chl) a, Chl b, Chl a + b. and caroten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Chen et al [38] observed chloroplast ultrastructural changes in C. medica using transmission electron microscopy and found chloroplast ultrastructural alterations, including their swelling, matrix zone expanding and lamella structure loosening. In moderately heat-tolerant P. lactiflora , few intact cellular structures were observed, most of the chloroplasts were swollen and assumed a near spherical shape, and their membranes were decomposed, which caused leakage of the grana lamellaes under high temperature stress [20]. In this study, PlHSP70 -overexpressing transgenic lines had more intact cell membranes, chloroplasts and starch grains and fewer plastoglobulis than WT, which was consistent with our observation of the yellow leaves in WT.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Chen et al [38] observed chloroplast ultrastructural changes in C. medica using transmission electron microscopy and found chloroplast ultrastructural alterations, including their swelling, matrix zone expanding and lamella structure loosening. In moderately heat-tolerant P. lactiflora , few intact cellular structures were observed, most of the chloroplasts were swollen and assumed a near spherical shape, and their membranes were decomposed, which caused leakage of the grana lamellaes under high temperature stress [20]. In this study, PlHSP70 -overexpressing transgenic lines had more intact cell membranes, chloroplasts and starch grains and fewer plastoglobulis than WT, which was consistent with our observation of the yellow leaves in WT.…”
Section: Discussionsupporting
confidence: 89%
“…Under high temperature stress, HSPs are synthesized and accumulated, and their contents are increased when the plants experience either abrupt or gradual increases in temperature [31]. In our previous studies, the expression levels of PlHSP70 were all detected in P. lactiflora subjected to long-term high temperature stress, and the results showed that they all increased gradually in the early stages and then decreased [20, 21]. Whereas in this study, the potted P. lactiflora was treated under short-term high temperature stress, the expression level of PlHSP70 increased gradually with the treatment, and no decline was observed.…”
Section: Discussionmentioning
confidence: 99%
“…P. lactiflora favors sunny environments while avoiding summer high temperature, often leading to high temperature stress in south China environments (Zhang et al 2016). In this respect, the effects of high temperature stress on P. lactiflora physiology and biochemistry were investigated, and it was found that high temperature-tolerant P. lactiflora cultivars could effectively reduce stress damage by enhancing antioxidant enzyme activities and heat shock protein gene expression (Wu et al 2016). Moreover, transcriptome and digital gene expression analysis of P. lactiflora were used to screen for thermo-tolerant-related differentially expressed genes (Hao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the abiotic stress resistance of Paeonia has mainly focused on plant responses to low versus high temperature, drought, salt, and heavy metals. Under high-temperature (35.75/27.5°C, average daily maximum/minimum temperature) stress, heatresistant P. lactiflora 'Zifengyu' showed enhanced activity of antioxidant enzymes (superoxide dismutase, peroxidase, and catalase) and the expression of HSP, which removed reactive oxygen species effectively and prevented plants from dying 169,170 . HSP70-overexpressing transgenic plants were tolerant to high temperature 171,172 .…”
Section: Abiotic Stress Resistancementioning
confidence: 99%